Muscle power factors and VO2max as determinants of horizontal and uphill running performance - Paavolainen, L.; Nummela, A.; Rusko, H. (Scandinavian Journal of Medicine & Science in Sports, 2000)
This study was carried out to investigate the importance of maximal oxygen uptake (VO2max) and so-called muscle power factors relating to neuromuscular and anaerobic characteristics as determinants of peak horizontal and uphill treadmill running velocity (Vmax). Muscle power factors were measured as peak velocity (VMART) and blood lactate concentration (BlaMART) in a maximal anaerobic running test and as maximal 30-m run velocity (V30m). Seven middle-distance runners, eight triathletes and eight cross-country skiers performed an incremental VO2max-test at horizontal (subscript max0) and 7 degrees uphill (subscript max7) and the MART at 3 degrees uphill on a treadmill and V30m-test on a track. The MART consisted of n x 20-s runs with a 100-s recovery between the runs and the velocity was increased by 0.41 m x s(-1) for each consecutive run until exhaustion. At 0 degrees Vmax was significantly higher but VO2max, ventilation and Bla were significantly lower than at 7 degrees inclination. Vmax0 correlated with VMART (r=0.85, P<0.001), Blamax0 (r=0.49, P<0.05) and V30m (r=0.78, P<0.001) but not with VO2max0. Vmax7 correlated with VO2max7 (r=0.78, P<0.001), VMART (r=0.61, P<0.01) and V30m (r=0.53, P<0.05). VMART correlated with BlaMART (r=0.71, P<0.01) and V30m (r=0.96, P<0.001) but not with VO2max0 or VO2max7. Middle-distance runners had a significantly (P<0.001) higher Vmax0, VMART BlaMART and V30m than triathletes and cross-country skiers, but no significant differences were found between the three groups in VO2max0, VO2max7 or Vmax7. We conclude that so-called muscle power factors, e.g. VMART, V30m and BlaMART, contribute to peak treadmill running performance and especially to horizontal running performance and that VO2max contributes more to uphill than horizontal running performance.